Calmidazolium, a calmodulin inhibitor, inhibits endothelium-dependent relaxations resistant to nitro-L-arginine in the canine coronary artery. - Illiano, S. (1992)
1. The role of calmodulin in endothelium-dependent relaxations in the canine coronary artery, was investigated by use of the inhibitor of calmodulin, calmidazolium. 2. The endothelium-dependent relaxations to adenosine diphosphate (ADP) and nebivolol, a beta-adrenoceptor antagonist, in control solution, and to bradykinin in high potassium solution (to inhibit endothelium-dependent hyperpolarization), were abolished by nitro-L-arginine (30 microM), an inhibitor of nitro oxide-synthase. Calmidazolium (10 microM) did not inhibit these relaxations. 3. Calmidazolium did not affect the endothelium-independent relaxations to SIN-1, an exogenous donor of nitric oxide (NO). 4. The relaxations to bradykinin and to the calcium ionophore A23187 in control solution were inhibited to a small extent by calmidazolium (10 microM). 5. Bradykinin and A23187 induced relaxations in the presence of nitro-L-arginine (30 microM) that were abolished by calmidazolium (10 microM) but not affected by glibenclamide (10 microM), an inhibitor of ATP-sensitive K+ channels. 6. The endothelium-independent relaxations to lemakalim, an ATP-sensitive K+ channel opener, were not affected by calmidazolium (10 microM) but were inhibited by glibenclamide (10 microM). 7. These results suggest that calmidazolium does not inhibit the endothelium-dependent relaxations due to endothelium-derived NO in the canine coronary artery but inhibits either the production of endothelium-derived hyperpolarizing factor (EDHF) from endothelial cells or its effects on vascular smooth muscle cells. Furthermore these results suggest that EDHF contributes to endothelium-dependent relaxations in the canine coronary artery.